2009
DOI: 10.1021/ja902799u
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear Intermediates in Oxidation Reactions: [(Me3SiC≡C)Me2(bipy)Pt−PtMe2(bipy)]+ in the Oxidation of PtIIMe2(bipy) (bipy = 2,2′-Bipyridine) by IPh(C≡CSiMe3)(OTf) (OTf = Triflate)

Abstract: A study of the reaction of PtMe(2)(bipy) with IPh(C[triple bond]CSiMe(3))(OTf) at low temperature in acetone, leading to detection of the Pt-Pt-bonded cation [Pt(2)Me(4)(C[triple bond]CSiMe(3))(bipy)(2)](+), an intermediate in the oxidation of Pt(II) to Pt(IV), is reported. The cation is assessed as Pt(III)-Pt(III) <--> Pt(IV)-Pt(II), and at the other extreme may be regarded as a cationic alkynylplatinum(IV) center, "[Pt(IV)Me(2)(C[triple bond]CSiMe(3))(bipy)](+)", stabilized by "Pt(II)Me(2)(bipy)" as a donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 38 publications
(23 reference statements)
3
64
0
Order By: Relevance
“…[28] To obtain more thermally stable complexes, the sixth coordination site of the platinum(IV) center has to be occupied by an additionally added anionic donor like iodide [28] or an neutral N donor like pyridine [29] because the anionic part of the alkynyliodonium salts requires the incorporation of nonnucleophilic anions like triflate, tetrafluoridoborate, or tosylate. [30] The use of diacetylplatinum(II) complexes with κ 2 -coordinated tris(pyrazolyl)methane ligands in such reactions should open the possibility to synthesize cationic alkynyl platinum(IV) complexes when the pendant pyrazolyl ring coordinates to the sixth coordination site.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[28] To obtain more thermally stable complexes, the sixth coordination site of the platinum(IV) center has to be occupied by an additionally added anionic donor like iodide [28] or an neutral N donor like pyridine [29] because the anionic part of the alkynyliodonium salts requires the incorporation of nonnucleophilic anions like triflate, tetrafluoridoborate, or tosylate. [30] The use of diacetylplatinum(II) complexes with κ 2 -coordinated tris(pyrazolyl)methane ligands in such reactions should open the possibility to synthesize cationic alkynyl platinum(IV) complexes when the pendant pyrazolyl ring coordinates to the sixth coordination site.…”
Section: Synthesismentioning
confidence: 99%
“…Synthesis of alkynyl(dimethyl)platinum(IV) complexes. [28] yl)platinum(IV) complexes 8 (Scheme 5). The reactions were performed at -78°C in dichloromethane, and after addition of the first drops of the alkynyliodine(III) reagent, the color of the reaction mixture immediately turned dark red.…”
Section: Synthesismentioning
confidence: 99%
“…5,6 However, these reactions very often follow an S N 2 pathway, 7−11 with the metal center acting as nucleophile through the filled d z 2 orbital. In addition, Puddephatt and Canty have shown that OA to Pt(II) complexes of planar diimines follow a binuclear stepwise mechanism, with two π−stacked units involved in the initial oxidation step, 12,13 providing evidence of the role of metallophyllic interactions on the chemical reactivity of mononuclear d 8 complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Stang and co-workers also demonstrated that reaction of platinum(0) complex 20 with alkynyliodonium triflate yielded alkynyl platinum(II) complexes after careful optimization of the reaction conditions (Scheme 2.10, A [92]). Canty and co-workers then further used the strong oxidizing properties of alkynyliodonium salts to access alkynyl-metal complexes in high oxidation states [93][94][95][96][97][98]. They first demonstrated that platinum(II) pincer complex 21 could be oxidized to platinum(IV) alkynyl complex 22 in 91% yield using alkynyliodonium triflate 14 as reagent (Scheme 2.10, B [93]).…”
Section: Alkynylation Of Metalsmentioning
confidence: 99%
“…They were also able to synthesize the corresponding palladium(IV) complex 25 and characterize it at low temperature, as it decomposed readily at room temperature [94]. In 2009, Canty and co-workers were also able to characterize a rare Pt dimer complex 27 at -80 °C, obtained by reacting Pt(II) bipyridine complex 26 with half an equivalent of alkynylodonium triflate 14 (Scheme 2.11) [98]. In principle, 27 can be considered as either a Pt(III) or a Pt(II)-Pt(IV) dimer.…”
Section: Alkynylation Of Metalsmentioning
confidence: 99%